2016
DOI: 10.1080/14735903.2016.1152062
|View full text |Cite
|
Sign up to set email alerts
|

Achieving successful farmer engagement on greenhouse gas emission mitigation

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.Achieving successful farmer engagement on greenhouse gas emission mitigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…They recognised that all eight measures they considered have different levels of costs, benefits and possible tradeoffs, which might have influenced their adoption. Burbi et al (2016) found similar results. This is corroborated by findings in our research, showing that there is a positive relationship between the implementation of energy saving measures and 'cost saving' as a motivation for taking action.…”
Section: Familiar With Campaign In 2015supporting
confidence: 62%
See 3 more Smart Citations
“…They recognised that all eight measures they considered have different levels of costs, benefits and possible tradeoffs, which might have influenced their adoption. Burbi et al (2016) found similar results. This is corroborated by findings in our research, showing that there is a positive relationship between the implementation of energy saving measures and 'cost saving' as a motivation for taking action.…”
Section: Familiar With Campaign In 2015supporting
confidence: 62%
“…precise dosage and timing of fertilisers) or methane emission reduction by the digestion of manure (Smith et al 2014). While energy saving measures are relatively simple and usually cost-effective, many studies have underlined the complexity and uncertain effects of non-CO 2 GHG measures (Fellmann et al 2018;Burbi et al 2016;de Boer et al 2011). However, in farmer-related behavioural studies, only few studies distinguish in the analyses between different types of measures (Haden et al 2012).…”
Section: Types Of Climate Change Mitigation Measures In Agriculturementioning
confidence: 99%
See 2 more Smart Citations
“…Although specific barriers vary with environmental, economic and farming system contexts (Feliciano et al, 2014), recent work suggests that categorisations of challenges developed from local studies have relevance at the global level (Kipling et al, 2019). An increasing body of work has focussed on identifying such challenges by gathering information from stakeholders (Burbi et al, 2016) and exploring their preferences in terms of the changes to be implemented (Jones et al, 2013). Other studies have focussed on costs, benefits and uncertainty in the effects of changes, supporting the prioritisation of the most economically effective mitigation measures (Eory et al, 2018;Jones et al, 2015).…”
Section: Introductionmentioning
confidence: 99%